2021
DOI: 10.2337/dc20-2623
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Simplification From a Basal-Bolus Insulin Regimen to a Fixed-Ratio Formulation of Basal Insulin Plus a GLP-1RA or to Basal Insulin Plus an SGLT2 Inhibitor: BEYOND, a Randomized, Pragmatic Trial

Abstract: OBJECTIVE BEYOND trial evaluated the feasibility of either basal insulin plus glucagon-like peptide 1 receptor agonist (GLP-1RA) or basal insulin plus sodium–glucose cotransporter 2 inhibitor (SGLT2i) to replace a full basal-bolus insulin (BBI) regimen in participants with type 2 diabetes and inadequate glycemic control. RESEARCH DESIGN AND METHODS Participants were randomized (1:1:1) to: 1 ) intensification of the BBI regimen ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
2
24
0
4
Order By: Relevance
“…The three new drugs were also likely to have caused the decreased use of sulfonylureas, αGI and pioglitazone, in line with reports from other countries 8 25–27. These new drugs could offer much better glycemic control with decreasing postprandial hyperglycemia, less hypoglycemia, and less weight gain, and often provide benefits with a smaller dose of insulin in insulin-treated patients 34–36. Clinical advantages and adverse effects should be taken into consideration for individualization of glycemic control, cost-effectiveness, and health management to explore the positioning of these new drugs within older established therapies 37…”
Section: Discussionmentioning
confidence: 64%
“…The three new drugs were also likely to have caused the decreased use of sulfonylureas, αGI and pioglitazone, in line with reports from other countries 8 25–27. These new drugs could offer much better glycemic control with decreasing postprandial hyperglycemia, less hypoglycemia, and less weight gain, and often provide benefits with a smaller dose of insulin in insulin-treated patients 34–36. Clinical advantages and adverse effects should be taken into consideration for individualization of glycemic control, cost-effectiveness, and health management to explore the positioning of these new drugs within older established therapies 37…”
Section: Discussionmentioning
confidence: 64%
“…Finally, the randomized, pragmatic, pilot BEYOND study provided evidence that it is possible and safe to switch from a basal-bolus regimen to a FRC. In fact, after 6 months, a similar HbA1c reduction (-0.6%) was obtained in patients intensifying previous basal-bolus therapy versus those switching to FRC (iGlarLixi or iDegLira), with lower insulin doses (62 U versus 27 U), fewer daily injections, and less hypoglycemia (17.8% versus 7.8% of patients with at least one episode) in the FRC group than in the basal-bolus group [20].…”
Section: Comparisons With Existing Knowledgementioning
confidence: 68%
“…Existing literature also showed that iGlarLixi is effective irrespective of age, diabetes duration, and ethnicity [18][19][20], and that iGlarLixi has an enhanced gastrointestinal tolerability compared with the single-agent GLP1-RA [18,19,[21][22][23][24].…”
Section: Comparisons With Existing Knowledgementioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, data reported from US real-world practice showed that patients on more than one insulin injection daily were able to switch to IDegLira without compromising on glycemic control (HbA 1c change of − 0.16%) [ 16 ]. Accordingly, the randomized pragmatic BEYOND trial recently demonstrated that switching from MDI (basal-bolus) regimen to either a once-daily fixed-ratio BI plus GLP-1RA combination or once-daily gliflozin plus BI scheme is safe and non-inferior to basal-bolus titration in terms of HbA 1c reduction, at least during the first 6 months of follow-up [ 22 ]. Demonstrating improved HbA 1c level (− 0.8%) and decrease in body weight (− 1.4 kg) in the MDI subgroup, the present study also provides data supporting the relevance of such a therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%